Shedding some light on photovoltaic solar energy in Africa – A literature review. (November 2018) - Brunet, Carole; Savadogo, Oumarou; Baptiste, Pierre; Bouchard, Michel A.
Abstract: Bearing in mind that there is increasingly abundant literature on the evolution of photovoltaic solar energy in Africa, it is necessary to make a global assessment with a focus on the path already traveled. This article reviews the literature on solar energy within the context of the African continent between 1992 and 2016. Based on the diversity of the articles analyzed, there are three main axes which emerge, namely: (i) the current situation, (ii) specificities, and (iii) performance. These make it possible to pinpoint the challenges of the development of photovoltaic solar energy in a continent with a severe energy deficit. This review also allows us to better understand the extent to which photovoltaic solar energy contributes to the sustainable development of African countries. Highlights: Review of the literature on photovoltaic solar energy related to Africa. To what extent photovoltaic solar energy contributes to sustainabltabe development. Three main axes emerge: current situation, specificities, and performance.